Evaluation of Experiential Learning Implementation in Vocational Education Based on Student Learning Style - Syam, Makmur; Ada, Walem; Poerwanto, Poerwanto (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
The main problem faced by students in the vocational field is the lack of specificity in the scientific field that focuses on mastering the knowledge, skills, and attitudes needed in the world of work. In addition, the emphasis on learning by doing the role of the student-centred learning approach becomes less attention from educators. This study aims to develop and implement an experiential learning design in the nautical science program through student worksheets based on the Kolb experiential learning stages by considering the Felder- Silverman student learning style and analyzing student attitudes and responses after participating in learning activities. We used the field case study method (case study research) with qualitative descriptive data analysis techniques. The results showed that the learning style preferences of nautical science students from the learning style categories: (1) 87.41% were categorized as active; (2) 84.44% were categorized as visual; (3) 81.48% were categorized as sensing; and (4) 57.04% were categorized as sequential. The results also show that the experiential learning design is feasible for using learning models and learning material assessments. The implementation of experiential learning activities was carried out very well. Learning activities are carried out on force based on the stages of concrete experience, reflective observations, abstract conceptualization, and active experimentation. Students' attitudes and responses are positive towards the experiential learning design. Experiential activities help students learn Basic Mechanical Engineering Design (cognitive), and they like to participate in learning activities (affective). The experiential design is practical in learning, canin learning, career theory and practice learning. H o w e v e r , some students respond that experiential learning activities are less challenging and too much of a task because they prefer to avoid many tasks.